Why do Chinese enterprises make imitative innovation?—An empirical explanation based on government subsidies - Song, Feifei; Zhao, Changheng (Frontiers in Psychology, 2022)
The previous literature analyzed the widespread imitative innovation of Chinese enterprises from various perspectives, including enterprises' rational choice of cost-gain, property rights system, human capital and policy environment. However, this paper provides a brand-new perspective on government subsidies for the reasons behind the imitative innovation of enterprises. According to the statistics from Chinese enterprise-labor matching, we found that government subsidies stimulated enterprises to make “imitative innovation” through patent purchase rather than independent R&D. Government subsidies were used for low-risk “imitative innovation” because of enterprises' rent-seeking behavior, low R&D ability and the review of government subsidy projects. Based on the above conclusions, this paper suggests that the government should reduce or withdraw its intervention in enterprise innovation and implement the post-subsidy and post-evaluation mechanism for government-subsidized programs.